Colonial Relic or Dynamic Organisation? The Commonwealth of Nations and Conflict Resolution - Rodger, Jessica (Victoria University of Wellington Law Review, 2003)
This article examines in detail the ability of the Commonwealth of Nations to resolve conflicts within or between its member States. The organisation has continually emphasised its focus on adaptability, hence the main question of this article is whether or not the Commonwealth has adapted sufficiently to deal with the new kinds of conflict predominant in the world today. After looking at the organisation itself, the article moves on to examine regional organisations and the way in which they have adapted their conflict resolution capabilities in recent years. Specific instances of the Commonwealth’s involvement in conflict resolution are also examined. Finally, various recommendations are put forward regarding which areas the Commonwealth needs to work on in order to ensure that it is in fact a dynamic and adaptable conflict resolution body.